Morphology and genetics of pyloric gland adenomas in familial adenomatous polyposis. Issue 4 (13th December 2016) - Hackeng, Wenzel M; Montgomery, Elizabeth A; Giardiello, Francis M; Singhi, Aatur D; Debeljak, Marija; Eshleman, James R; Vieth, Michael; Offerhaus, G Johan; Wood, Laura D; Brosens, Lodewijk A A
Abstract : Aims: Gastric pyloric gland adenomas (PGAs) are rare epithelial polyps that are found more commonly in autoimmune atrophic gastritis and familial adenomatous polyposis (FAP). Little is known about the morphology and genetics of PGAs in FAP. PGAs in FAP are studied morphologically and genetically. Findings in FAP‐associated PGAs are compared to sporadic PGAs and related lesions such as oxyntic gland adenoma (OGA) to increase our understanding of these rare polyps. Methods and results: Seven PGAs and 18 fundic gland polyps (FGPs) from FAP patients were collected. KRAS and GNAS mutations were determined in six PGAs and 18 FGPs. Immunohistochemistry was applied on five PGAs to provide further confirmation of the histological subtypes and genetic alterations. Morphology of all PGAs was studied and compared to literature on sporadic PGAs and related lesions. All successfully sequenced PGAs (six of six) carried GNAS mutations and half of the successfully sequenced PGAs carried a KRAS mutation (three of six). Nuclear β‐catenin was seen only in one PGA with focal high‐grade dysplasia. Morphologically, PGAs in FAP showed overlapping features with OGA. Conclusion: Familial adenomatous polyposis‐associated PGAs have a similar genetic background as sporadic PGAs, i.e. KRAS and GNAS mutation. Based on morphological findings in FAP associated PGAs, it is hypothesized that PGAs and OGAs are closely related lesions.